2021
DOI: 10.1111/vde.13042
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis and immunotherapy of Culicoides hypersensitivity in horses: an update

Abstract: Culicoides hypersensitivity (CH) is a strongly pruritic dermatitis of horses, characterised histologically by mixed perivascular to diffuse cellular infiltrates of mononuclear cells and eosinophils, and caused by helper T cell (Th)2, immunoglobulin (Ig)E‐mediated reactions to antigens present in the saliva of biting Culicoides midges. As treatment of CH is still not satisfactory, a better knowledge of the pathogenesis of CH is needed for the development of new therapeutic modalities. Accordingly, availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…A clear preference to use single allergens over crude extract in serology has been determined for equine Culicoides hypersensitivity, but was not indicated here for EA using eight selected A. fumigatus antigens ( 25 ). The different A. fumigatus antigens tested here were mainly similar to each other regarding their immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clear preference to use single allergens over crude extract in serology has been determined for equine Culicoides hypersensitivity, but was not indicated here for EA using eight selected A. fumigatus antigens ( 25 ). The different A. fumigatus antigens tested here were mainly similar to each other regarding their immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, their advantage over A. fumigatus lysate as an antigen source for IgG and IgA serology was small in this study. It is possible that IgA- and IgG-inducing A. fumigatus antigens detected in this approach are more diverse than IgE-inducing allergens ( 25 , 73 ). A lack of dominating A. fumigatus antigens in EA would complicate antigen-specific therapeutic strategies as well as diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When an allergic subject with prior exposure to the allergen, on re-exposure to the allergen, there is cross-linking of IgE bound to high affinity FcεRI receptors on mast cells leading to release of different mediators, causing the clinical signs of immediate hypersensitivity. Infiltration of leucocytes such as T helper 2 (Th2) cells, eosinophils and basophils at the site of the allergic reaction is followed by late-phase reaction peaking 24 h post exposure (Marti et al, 2021). Furthermore, with regards to earlier studies on the immunopathology of IBH, they was reported increase in the population of CD4+, Langerhans, and eosinophil cells in the skin (McKelvie et al, 1999).…”
Section: Immunopathogenesis and Cellular Responses In Ibhmentioning
confidence: 95%
“…Under the effect of these cytokines, antigen presenting cells (APC) direct the immune response towards the production of IL-4 and IL-13 with the help of helper T cell (Th)2. Subsequently, B cells undergo class switch to produce allergen-specific IgE that binds to high affinity FcεRI receptors on mast cells and basophils leading to sensitization (Marti et al, 2021). When an allergic subject with prior exposure to the allergen, on re-exposure to the allergen, there is cross-linking of IgE bound to high affinity FcεRI receptors on mast cells leading to release of different mediators, causing the clinical signs of immediate hypersensitivity.…”
Section: Immunopathogenesis and Cellular Responses In Ibhmentioning
confidence: 99%